Emotional Transformation and Cognitive Resilience of the Main Character in the Short Story Making a Mushroom House through Maria Nikolajeva's Perspective - Saputri , Endang Ika; Indriyani, Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Disappointment arising from unfulfilled expectations is a common emotional challenge for children, yet it possesses the potential to become a catalyst for creativity if managed appropriately. This study aims to analyze the emotional transformation of the main character in the short story Membuat Rumah Jamur by Indri Riskika Muliatama through Maria Nikolajeva’s cognitive psychological perspective. Employing a descriptive qualitative method, the research dissects the mechanism of the protagonist's emotional trajectory and the inherent moral values emerged during this process. The analysis reveals that the text effectively depicts a cognitive shift from a low point (disappointment due to a canceled vacation) to a high point (creative satisfaction through handicraft making). Through Nikolajeva’s concept of narrative empathy, it is found that the narrative facilitates child readers in performing emotional reframing—reinterpreting negative situations into innovative opportunities. Furthermore, this transformation internalizes values of patience, harmony, and resilience. The study concludes that the KKPK children’s literature series functions as a crucial emotional laboratory for developing children's mental toughness and creativity amidst complex social dynamics.